PRE-SERVICE ENGLISH TEACHERS' PERCEPTIONS TOWARD MICROTEACHING PROGRAM: A Case Study at English Study Program of the University of PGRI Pontianak - Hadiana; Abdul Arif; Tri Kurniawati (Program Studi Pendidikan Bahasa Inggris, 2025)
This study aims to explore the perceptions of pre-service English teachers toward the microteaching program, focusing on its influence on their professional learning, its role in preparing them for field teaching practice, and the challenges and supports they experienced. The study employed a qualitative case study design. Eight pre-service teachers undertaking micro teaching program were purposively involved as the research participants. Data were collected through semi-structured interviews and reflective journals, and analyzed using thematic analysis (Braun & Clarke, 2006). The findings revealed that microteaching was initially seen not only as a basic academic requirement, but also as a valuable simulation of real teaching practice. The program significantly enhanced their teaching-related skills, pedagogical knowledge, and personal growth, including of confidence, communication, classroom management, and lesson planning. Moreover, microteaching helped participants build professional readiness for their field teaching practice (PLP 2). However, some challenges such as time constraints and limited resources were also reported. To address these, participants relied on self-reflection, peer support, and guidance from supervisors. This study highlights the critical role of microteaching in bridging the gap between theory and practice in teacher education and offers insights into how the program can be improved to better support future educators. Keywords: Pre-service teachers, microteaching, perceptions, professional learning, teaching practicum.